Captopril in clinical hypertension. Changes in components of renin-angiotensin system and in body composition in relation to fall in blood pressure with a note on measurement of angiotensin II during converting enzyme inhibition. Issue 3 (September 1980) - Atkinson, A B; Morton, J J; Brown, J J; Davies, D L; Fraser, R; Kelly, P; Leckie, B; Lever, A F; Robertson, J I
Abstract : The effect of the converting enzyme inhibitor captopril on arterial pressure, the components of the renin-angiotensin-aldosterone system, and body sodium and potassium content was studied in eight hypertensive patients with renal artery stenosis and, in conjunction with diuretics, in seven patients with hypertension unresponsive to previous treatment. Two hours after the first dose, captopril caused significant falls in systolic and diastolic pressures, plasma angiotensin II, and aldosterone, with converse increases in angiotensin I and both active and total renin; the initial fall in diastolic pressure was significantly related to the drop in plasma angiotensin II. The biochemical changes were sustained during prolonged treatment, even when diuretics were added. One untreated patient with renal artery occlusion had severe secondary aldosterone excess, was sodium and potassium depleted, and severely hyponatraemic and hypokalaemic; captopril restored blood pressure, plasma electrolyte concentrations, and exchangeable sodium and total body potassium to normal. In one man with renal artery stenosis and overall renal impairment captopril led to sodium retention, and blood pressure did not fall until a diuretic was added. In the remaining patients with renal artery stenosis, pretreatment renin, angio tensin II, and aldosterone concentrations were either normal or only modestly raised, and plasma electrolyte concentrations and body content of sodium and potassium were normal. Captopril alone controlled arterial pressure in all, three cases showing a gradual fall of pressure over the first six weeks of treatment; no significant changes in exchangeable sodium or total body potassium were seen. The group of patients with previously intractable hypertension were all controlled with a combination of captopril and diuretic.